Research productivity and impact of Library and Information Science in the Web of Science - Erfanmanesh, M.A.; Didegah, F.; Omidvar, S. (Faculty of Computer Science & Information Technology, University of Malaya, 2010)
This study aims to investigate world scientific productivity of LIS researchers, their visibility and impact of their publications. A total of 99789 documents published in 61 LIS journals were extracted from WoS during 1998-2007 and were then analyzed. Based on the results, no significant differences were found among frequencies of LIS publications in different years. The results of Chi-square test clearly proves this finding (Chi(2) value=.001, df=9, p>.05). The growth rate of LIS citations showed that the number of citations has grown more than the number of LIS publications over the period under consideration. The number of citations received by each LIS publication was 0.27 on average. More than 60 percent of all LIS publications and about 40 percent of all citations to LIS were made by US researchers. Computer Science researchers have mostly cited LIS publications in their research. Among all institutions, The Scientist is the most productive institution in LIS. In addition, more than 60 percent of LIS papers were published in Library Journal.